IOP Conference Series: Earth and Environmental Science - Malchik specialist in the field of ecology and life safety Associate Professor of Yurga technological Institute of Tomsk Polytechnic University, candidate of technical sciences; Litovkin specialist in the field of ecology and life safety assistant of Yurga technological Institute of Tomsk Polytechnic University; Rodionov specialist in the field of ecology and life safety senior lecturer of Yurga technological Institute of Tomsk Polytechnic University, candidate of pedagogical sciences; Kryuchkova (2018)
Within the research, SiO2-Ta2O5 films from film-forming solutions based on tetraethoxysilane and tantalum chloride (V) are synthesized. Physicochemical patterns and specifics of producing the films are determined by means of IR spectroscopy and thermogravimetric analysis. The processes of SiO2-Ta2O5 films formation are studied. Interrelation between SiO2-Ta2O5] composition, concentration of incoming components and their physicochemical properties are revealed.